2011
DOI: 10.1161/circinterventions.110.958090
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Staining Outside the Sirolimus-Eluting Stent Leading to Coronary Aneurysm Formation

Abstract: A 69-year-old man with prior myocardial infarction (hypertension; dyslipidemia; smoking; no diabetes; and no history of allergy, autoimmune disease, or vasculitis) underwent sirolimus-eluting stent (SES) implantation (3.0 mm in diameter; 33 mm in length) for chest pain on exertion with chronic total occlusion of the left anterior descending coronary artery (LAD) ( Figure 1A through 1C and Video 1). Intravascular ultrasound examination after SES implantation demonstrated well-expanded stent struts without evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…More recently, Kon et al reported a case with VLST of SES demonstrating serial changes in PSS leading to aneurysm formation, as well as histopathological evidence of hypersensitivity vasculitis in the stented segment. 22 Therefore, accumulating evidence suggests that VLST associated with ISA and/or PSS might be mechanistically related to chronic inflammatory reactions. Inflammation leading to destruction of the medial wall might lead to loss of elastic vessel integrity and aneurismal dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kon et al reported a case with VLST of SES demonstrating serial changes in PSS leading to aneurysm formation, as well as histopathological evidence of hypersensitivity vasculitis in the stented segment. 22 Therefore, accumulating evidence suggests that VLST associated with ISA and/or PSS might be mechanistically related to chronic inflammatory reactions. Inflammation leading to destruction of the medial wall might lead to loss of elastic vessel integrity and aneurismal dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of ISA including positive arterial remodeling, vessel wall injury at stent implantation, dissolution of jailed thrombus or plaque debris, and hypersensitivity reaction of coronary artery have been proposed, 2,4,5,21 but the mechanism of PSS is still unclear. Kon et al 4 reported a case with PSS in a lesion after SES implantation.…”
Section: Discussionmentioning
confidence: 99%
“…We named this finding peri-stent contrast staining (PSS), which is an angiographical finding of contrast medium stain outside the stent being >20% of the stent diameter, and it has been preliminary reported that PSS after sirolims-eluting stent (SES) implantation could predict late stent thrombosis of the lesion with PSS. 3 Although it was unclear what PSS consisted of, Kon et al 4 reported that a case with PSS had histopathological evidence of hypersensitivity reaction in the lesion after SES implantation.…”
mentioning
confidence: 99%
“…5,26- 28 Kon et al reported a case of VLST with ISA, and after pathologic evaluation they proposed that chronic inflammation and hypersensitivity vasculitis might be important underlying mechanisms of ISA. 4 As described before, an abnormal vascular response mainly composed of inflammation is thought to be prolonged at the PSS site. Therefore, we infer that PSS is a result of inflammatory reaction to the polymer or drug.…”
Section: Angioscopic Findingsmentioning
confidence: 85%